Federations: Shared Rule and Self-rule in the Search for Stable Governance - de Villiers, Bertus (2012)
In a world searching for stability, federations have flourished in situations of diversity, where flexibility and adaptability are required within the confines of national unity. Federations do not have the monopoly to accommodate diversity, but the essence of the philosophy that underpins federations is supportive of the existence of multiple identities, constitutional guarantees for power-sharing and self-rule, constitutionalism and judicial oversight. These are all elements that are attractive to many emerging democracies. This article investigates the reasons why federation has become so popular in young, developing democracies. The article concludes that the twin-characteristics of federations-constitutionally guaranteed 'shared rule' and 'self-rule'-are essential ingredients and building blocks in a world where many emerging democracies are yearning for stability. © 2012 Copyright South African Association of Political Studies.